ANALISIS PELAKSANAAN FUNGSI BADAN PENGELOLA PERBATASAN DAERAH DI KABUPATEN KEPULAUAN MERANTI TAHUN 2011-2013 - ", Izwan; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to determine and analyze the performance of the functions of Border Management Agency District Meranti Islands to the problems that occurred in the border area for example, concerning the environment, especially coastal erosion, infrastructure development, security and defense in 2011-2013. This study focused on Border Management Agency District Meranti Islands. With the formulation of research problems, namely how the implementation of the functions of the Regional Border Management Agency in Meranti Islands District Year 2011-2013 and inhibiting factors in the implementation of the functions of the Regional Border Management Agency in Meranti Islands District Year 2011-2013.This research is descriptive in which researchers provide a description and picture of the phenomenon or social phenomena studied by describing the independent variables systematically and accurately. The method of data collection is done by in-depth interview, participant observation, and documentation.These results indicate that the function of Border Management Agency District Meranti Islands in the exercise of its functions to the border area is not in line with the objectives and targets set. It does not fit with the vision and mission of the Border Management District Meranti Islands. Resulting in maximal performance of the functions of Border Management Agency District Meranti Islands to the border area.Keywords: implementation, functions, Border Management Agency